Parental and provider vaccine hesitancy and non-timely childhood vaccination in Switzerland. Issue 23 (20th May 2022) - Jafflin, Kristen; Deml, Michael J.; Schwendener, Corina L.; Kiener, Laura; Delfino, Alexandre; Gafner, Rebecca; Schudel, Sophie; Mäusezahl, Mirjam; Berger, Christoph; Huber, Benedikt M.; Merten, Sonja; Tarr, Philip E.
Highlights: Vaccine hesitant parents tend to see vaccine hesitant providers. Provider vaccine hesitancy is associated with children's higher odds of non-timely vaccination. Parental vaccine hesitancy is associated with children's higher odds of non-timely vaccination. A higher the degree of parental and provider vaccine hesitancy is associated with increased odds of non-timely vaccination. Abstract: Objective: Although medical providers are a trusted vaccination information source for parents, they do not universally support vaccination. Complementary medicine (CM) providers are particularly likely to hold vaccine hesitant (VH) views, and VH parents often consult with them. Little research compares VH of parents and providers, and if and how each is associated with uptake of recommended childhood vaccines. Methods: We defined non-timely receipt as recommended vaccines given > 1 month later than officially recommended, based on vaccination records. We administered versions of the Parent Attitudes about Childhood Vaccines (PACV) 5-item survey instrument to 1256 parents and their children's pediatricians (N = 112, 40 CM-oriented, 72 biomedical [not CM-oriented]) to identify moderately (PACV-score 5–6) and highly (PACV-score 7+) hesitant providers/parents. We obtained multivariable adjusted odds ratios to test relationships between parental VH and provider type/VH, and between non-timely receipt of selected childhood vaccines and parental VH and provider type/VH. Results: No biomedical providers were VH, 9 CM providers were moderately VH, and 17 were highly VH. Parents seeing moderately and highly hesitant providers had adjusted odds ratio (AOR) for being VH = 6.6 (95% confidence interval (CI), 3.1–14.0) and AOR = 31.3 (95% CI 16.8–58.3), respectively. Across all vaccine uptake endpoints, children of moderately and highly hesitant parents had 1.9–3.8 and 7.1–12.3 higher odds of non-timely vaccination, and children seeing highly hesitant CM providers had 4.9–9.4 higher odds. Children seeing moderately hesitant CM providers had 3.3 higher odds of non-timely vaccination for the 1st dose of measles and 3.5 higher odds for 1st dose of polio/pertussis/tetanus. Conclusion: VH by both parents and providers each is associated with non-timely childhood vaccination. As VH parents are more likely to consult with VH providers, interventions aimed at increasing timely vaccination need to primarily target VH providers and their clients.